Innovation for environmental sustainability in South African building practices - Nel, Marius (My University, 2015)
The purpose of this research is to conduct a study into the innovative and sustainable building practices in the South African construction industry. The aim of the study is to establish why and how firms in the construction industry innovate using sustainable and environmentally friendly building practices. The study will consider the determinants and the nature of adopting and implementing these practices that arise from innovation to promote sustainability in the construction industry. This study employs a qualitative research strategy. The study employs one-onone in-depth interviews with key project team members that were involved in six green star rated buildings in Gauteng, South Africa. Interviews were conducted with property developers, architects, electrical engineers, mechanical engineers, wet services engineers, green star and sustainability consultants, building contractors and industry specialists. The findings suggest that tenants, clients and developers are the main drivers and initiators of sustainable and green building practices. Large corporates are also seen to be some of the biggest drivers and initiators because of corporate governance and marketing. The industry is recognising the benefits of green buildings in terms of energy saving, better internal environmental quality, productivity, higher rental and better return on assets. Although there is a greater cost associated with going green, the benefits all have a positive financial return on investment. Short term cost considerations are still evident, but many in the industry are looking at and realising the long term benefits. Regulation and policy plays an important role in promoting sustainable building practices. Firms innovate through capability building, training, knowledge transfer and collaboration. Firms have seen the opportunities and have adapted to the uncertainties and changes in the market place by adapting their strategies and organisational direction accordingly. Firms that do not have the necessary resources or skills, make use of external sources as and when required, but also collaborate as a team to drive the project to a successful conclusion.
Keywords: Sustainable buildings -- South Africa. Construction industry -- South Africa -- Management.